1981
DOI: 10.1113/jphysiol.1981.sp013630
|View full text |Cite
|
Sign up to set email alerts
|

Site(s) and ionic basis of α‐autoinhibition and facilitation of [3H]noradrenaline secretion in guinea‐pig vas deferens

Abstract: SUMMARY1. Mechanisms controlling the secretion of [3H]noradrenaline from the noradrenergic nerves of guinea-pig isolated vas deferens, prelabelled by incubation with [3H]noradrenaline, were studied using (a) different modes of (extramural or transmural) electrical nerve stimulation (a total of 300 shocks of varying strength, and a duration of 2 msec) at or (b) depolarizing concentrations of K+ (60-110 mM).2. The fractional rise in efflux of 3H-labelled material (At) was used to measure the secretion of [3H]n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
53
1

Year Published

1982
1982
1993
1993

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 132 publications
(58 citation statements)
references
References 84 publications
4
53
1
Order By: Relevance
“…When slices were superfused with KRB solution containing TTX (10-6 M), a high K+-evoked release of Glu was suppressed to 35% of that observed in control medium, with no change in the spontaneous release (Figure 2a). TTX prevents nerve conduction by blocking the sodium channels (Narahashi, 1974), therefore, the insensitive component of Glu release to TTX was presumably due to direct depolarization of the nerve terminals (Blaustein et al, 1972;Alberts et al, 1981;1982). Subsequently, a series of experiments were carried out to investigate possible effects of a specific dopamine receptor agonist and antagonist on high K+-evoked Glu release.…”
Section: Discussionmentioning
confidence: 99%
“…When slices were superfused with KRB solution containing TTX (10-6 M), a high K+-evoked release of Glu was suppressed to 35% of that observed in control medium, with no change in the spontaneous release (Figure 2a). TTX prevents nerve conduction by blocking the sodium channels (Narahashi, 1974), therefore, the insensitive component of Glu release to TTX was presumably due to direct depolarization of the nerve terminals (Blaustein et al, 1972;Alberts et al, 1981;1982). Subsequently, a series of experiments were carried out to investigate possible effects of a specific dopamine receptor agonist and antagonist on high K+-evoked Glu release.…”
Section: Discussionmentioning
confidence: 99%
“…[3WH-NA overflow Alberts et al (1981). Previous investigations in rodent vas deferens have shown that [3H]-NA is the major constituent of the total radioactivity released upon stimulation of the tissue (Beattie et al, 1986;Kapocsi et al, 1987).…”
Section: Superfusion Studiesmentioning
confidence: 99%
“…Under these conditions, it has previously been shown that over 90% of the tritium present in the tissue after superfusion with Krebs solution is intact [3H]-NA (Alberts et al, 1981). The superfusate was collected in 2-min fractions.…”
Section: Electrophysiological Experimentsmentioning
confidence: 99%